Ensemble modelling reveals spiny monkey orange (Strychnos spinosa Lam.) as a vulnerable wild edible fruit tree in West Africa - Hospice Gérard Gracias Avakoudjo; Mahunan Eric José Vodounnon; Rodrigue Idohou; Aly Coulibaly; Achille Ephrem Assogbadjo (Geology, Ecology, and Landscapes)
This study aimed at modelling the historical distribution and assessing the potential impacts of future climate on spiny monkey orange (Strychnos spinosa Lam.) population across West Africa using the Shared Socio-economic Pathways (SSP 245 and SSP 585) scenarios at the 2041–2060- and 2081–2100-time horizons. Bioclimatic and soil variables were used at a resolution of 30 arcseconds with 588 occurrence records analysed using five algorithms (Random Forest (RF), Maximum Entropy (MaxEnt), Support Vector Machine (SVM), Boosted Regression Trees, and Generalized Linear Model (GLM)) and four global climate models (CanESM5, CNRM-CM6-1, HadGEM3-GC31-LL, and MIROC6). The Models’ performance was evaluated using the Area under the Curve (AUC), True Skill Statistic (TSS), Correlation coefficient (COR), and the Deviance. The most efficient algorithm (RF) was employed for the modelling, and the resulting maps were overlaid on the existing protected area network. The distribution modelling under future climate revealed an increase in the high and moderate suitability areas for S. spinosa at 2041–2060 and 2081–2100 horizons. Based on the results, Circa-situm conservation and ex-situ conservation strategy should be encouraged in addition to protected area network (PAN).